A study on the concentration and dispersion of PM10 in UTHM by using simple modelling and meteorological factors - Abd Rahman, Malek Faizal (2013)
Air pollution is the introduction of chemicals, particulate matter, or biological materials that cause harm or discomfort to humans or other living organisms, or cause damage to the natural environment or built environment, into the atmosphere. Air pollution can also be known as degradation of air quality resulting from unwanted chemicals or other materials occurring in the air. The simple way to know how polluted the air is to calculate the amounts of foreign and/or natural substances occurring in the atmosphere that may result in adverse effects to humans, animals, vegetation and/or materials. The objective of this study is to create a simulation of air quality dispersion in UTHM campus by using computer aided design mechanism such as software and calculating tools. Another objective is to compare the concentration obtained from the end result of calculation with past studies. The air pollutant in the scope of study is Particulate Matter (PM10). The highest reading recorded for E-Sampler was 305µg/m 3 . It was recorded in Structure Lab sampling point while the highest expected concentration by the Gaussian Dispersion Model was 184µg/m for UTHM Stadium. The recommended value for permissible exposure to particulate matter in 24 hours time is 150µg/m 3 3 according to the Recommended Malaysian Air Quality Guidelines.